High-fat-diet-induced obesity causes an inflammatory and tumor-promoting microenvironment in the rat kidney - Kerstin Stemmer; Diego Perez-Tilve; Gayathri Ananthakrishnan; Anja Bort; Randy J. Seeley; Matthias H. Tschöp; Daniel R. Dietrich; Paul T. Pfluger (The Company of Biologists, 2012)
SUMMARY Obesity and concomitant comorbidities have emerged as public health problems of the first order. For instance, obese individuals have an increased risk for kidney cancer. However, direct mechanisms linking obesity with kidney cancer remain elusive. We hypothesized that diet-induced obesity (DIO) promotes renal carcinogenesis by inducing an inflammatory and tumor-promoting microenvironment. We compared chow-fed lean Wistar rats with those that were sensitive (DIOsens) or partially resistant (DIOres) to DIO to investigate the impact of body adiposity versus dietary nutrient overload in the development of renal preneoplasia and activation of tumor-promoting signaling pathways. Our data clearly show a correlation between body adiposity, the severity of nephropathy, and the total number and incidence of preneoplastic renal lesions. However, similar plasma triglyceride, plasma free fatty acid and renal triglyceride levels were found in chow-fed, DIOres and DIOsens rats, suggesting that lipotoxicity is not a critical contributor to the renal pathology. Obesity-related nephropathy was further associated with regenerative cell proliferation, monocyte infiltration and higher renal expression of monocyte chemotactic protein-1 (MCP-1), interleukin (IL)-6, IL-6 receptor and leptin receptor. Accordingly, we observed increased signal transducer and activator of transcription 3 (STAT3) and mammalian target of rapamycin (mTOR) phosphorylation in tubules with preneoplastic phenotypes. In summary, our results demonstrate that high body adiposity induces an inflammatory and proliferative microenvironment in rat kidneys that promotes the development of preneoplastic lesions, potentially via activation of the STAT3 and mTOR signaling pathways.